The Transformation of Rabiah al-Adawiyah and Al-Ghazali's Thought in Islamic Sufism - Muh Idris (Pappaseng: International Journal of Islamic Literacy and Society, 2024)
This article aims to examine the thoughts of Rabiah Al-Adawiyah and Al-Ghazali. The research method used is Library Research (Literature Study). Primary data is obtained from literature searches related to the thoughts of Rabiah Al-Adawiyah and Al-Ghazali, while secondary data consists of other relevant references discussing these two figures.The research findings indicate that Rabiah Al-Adawiyah's Sufi teachings are centered on the concept of Mahabbah. The term Mahabbah originates from the root words ahabba,yuhibbu,mahabatan, which deeply signify love or profound affection. Additionally, al-mahabbah can also refer to an inclination towards something as a means of fulfilling spiritual needs. Regarding Al-Ghazali's thought, he frequently rejected certain ideas, which later became part of his creed. He criticized philosophy in his book Tahafut al-Falasifah (The Incoherence of the Philosophers), yet he himself engaged with and even supported philosophical ideas. When speaking with the Ash'arites, he appeared to be a pure Ash'arite. In Sufism, he embraced the path of a Sufi. This demonstrates that he often shifted perspectives and did not strictly adhere to a single school of thought. Consequently, Ibn Rushd criticized him, stating:"He did not remain steadfast in a single school of thought in his books. Instead, he became an Ash'arite with the Ash'arites, a Sufi with the Sufis, and a philosopher with the philosophers.